Towards a curriculum on responsible land administration - Mitchell, D. (2020)
Global challenges affecting and informing modern land administration systems include poverty reduction, and the challenges related to food and water insecurity, the growth of informal settlements and slums, climate change and natural disasters. However, land administration must adapt to support these global challenges in a way that is consistent with the international goals and instruments. This is the basis for the emerging concept of Responsible Land Administration. The outcome of the inception phase of this project and discussions at an Expert Group Meeting were agreement on the need for the development of a structured knowledge and learning base on Responsible Land Administration to support the strategic objectives of the capacity development strategy of the Global Land Tool Network (GLTN). The focus of this structured knowledge and learning base is on the emerging concept of Responsible Land Administration and this paper has outlined the proposed aims and structure of the knowledge and learning base, as well as the next steps for implementation.